2011
DOI: 10.1159/000335119
|View full text |Cite
|
Sign up to set email alerts
|

<i>SLC26A4</i> Genotypes and Phenotypes Associated with Enlargement of the Vestibular Aqueduct

Abstract: Enlargement of the vestibular aqueduct (EVA) is the most common inner ear anomaly detected in ears of children with sensorineural hearing loss. Pendred syndrome (PS) is an autosomal recessive disorder characterized by bilateral sensorineural hearing loss with EVA and an iodine organification defect that can lead to thyroid goiter. Pendred syndrome is caused by mutations of the SLC26A4 gene. SLC26A4 mutations may also be identified in some patients with nonsyndromic EVA (NSEVA). The presence of two mutant allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 51 publications
1
31
0
1
Order By: Relevance
“…SLC26A4 is required for adequate development of the inner ear [7,8] and it has been suggested that the carrier is involved in thyroid iodide transport [5,9,10]. Pendrin mediates anion transport in airways [11,12] and contributes to renal tubular anion transport [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…SLC26A4 is required for adequate development of the inner ear [7,8] and it has been suggested that the carrier is involved in thyroid iodide transport [5,9,10]. Pendrin mediates anion transport in airways [11,12] and contributes to renal tubular anion transport [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is defined through congenital SNHL or deafness and a malfunction of thyroid hormone synthesis. The genetic background is a mutation of the SLC26A4 gene, coding for a transmembrane protein with anion transport function, called Pendrin [3,4,5]. Pendrin is present in multiple organs, such as the kidney, the airways, the thyroid gland and the inner ear.…”
Section: Introductionmentioning
confidence: 99%
“…The over 160 known mutations of the SLC26A4 gene [4] can appear in a monoallelic or a biallelic fashion and lead to non-syndromic enlarged vestibular aqueduct (EVA) or Pendred syndrome [5]. Pendred syndrome is typically associated with biallelic mutations, whereas monoallelic mutations may lead to SNHL without further phenotypes [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations